Peningkatan Kemampuan Penalaran Matematika Dengan Pendekatan Scientific Terintegrasi Pada Model Problem Solving (PTK Terhadap Siswa Kelas VIII D Semester Gasal SMP Negeri 1 Wonosari Tahun Ajaran 2015/2016) - Aji Sulistyono, Danang; , Dra. Sri Sutarni, M.Pd (2016)
The purpose of this research improve the mathematical reasoning students ability the use of Scientific approach integrated by problem solving model. The method of research is qualitative study by design class action research (CAR). Subject this research is all students on the VIII D grade was conducted in SMP N 1 Wonosari consisted to 33 students study year 2015/2016. Collecting data by through observation, field notes, documentaries and tests. Analysis techniques the data used is the plot method consisting of data reduction, data presentation and data verification. The result showed can upgrading mathematical reasoning students. This improvement can be seen on indicators consist 1) students in asking for the first assumption before is 30,30% and at the end is 90,09% 2) students in discover pattern of problems before is 21,20% and at the end is 69,69% 3) students in doing manipulation mathematics before is 27,20% and at the end is 63,63% 4) students in drawing conclusion before is 18,20% and at the end is 66,66%. Conclusion of this research that the use of Scientific approach integrated by problem solving model can improve the ability mathematical reasoning students. Keywords : reasoning, scientific, problem solving